Comparison Of Pre-Test Values Before Study Assistance And Post Test After Learning Assistance Against The Concept And Application Of Circumference Circle (Class VIII Students Of Tamalabang Public Middle School) - Puling Tang, Melki Imamastri (International Research-Based Education Journal, 2023)
Mathematics learning is a teaching and learning process built by teachers to develop students' creative thinking that can improve students' thinking skills, and can construct new knowledge as an effort to improve good mastery of mathematical material, especially around circles. The purpose of this research is how the knowledge of class VIII SMP Negeri Tamalabang on the value of phi (π) and the ability to understand and solve problems related to determining the circumference of a circle. The research method used is descriptive qualitative. The form of descriptive research used is case research. The results showed that students' understanding in finding the value of phi and the formula for the circumference of a circle developed well from the comparison of pree test and post test. This learning design makes students look more active and begins to show the ability to express opinions even though the result is that there is a development in students' understanding. The average pree test and post test scores of 21 class VIII students of SMP Negeri Tamalabang were 55.05 for the average pree test and 84.76 for the pree test. This indicates that there is a well-developed understanding of the eighth grade students. In other words, many students understand the concept of the circumference of a circle or there is an increase in students' understanding in solving problems related to the circumference of a circle. There needs to be motivation that stimulates students to continue to study hard, especially in the field of mathematics.